The impact of autism spectrum disorder on parent employment: Results from the r‐Kids study. Issue 3 (22nd December 2022) - Lynch, Frances L.; Bulkley, Joanna E.; Varga, Alexandra; Crawford, Phillip; Croen, Lisa A.; Daida, Yihe G.; Fombonne, Eric; Hatch, Brigit; Massolo, Maria; Dickerson, John F.
Abstract: Parents of children with autism spectrum disorder (ASD) and other chronic health conditions often face exceptional caregiving demands that can lead to challenges related to maintaining and succeeding in employment. Detailed information on the specific ways in which these health conditions impact parent employment could aid in designing equitable, effective policies to support families. The r‐Kids study used electronic health records to identify three groups of children: those with ASD, asthma, or neither condition (control), from several health care systems. We oversampled racial and ethnic minorities and matched the asthma and control groups to the age and sex distribution of the ASD group. Parents completed three online surveys over the course of a year to measure annual employment outcomes. Surveys included the Family Economic Impact Inventory (measuring employment impacts) and measures of quality of life and symptom severity. All materials were provided in English and Spanish. The study enrolled 1461 families (564 ASD, 468 asthma, 429 control). Youth were 3–16.5 years old and predominantly male (79%). The sample was diverse (43% non‐Hispanic White; 35% non‐Hispanic Asian, Black, Native Hawaiian, or Other; and 21% Hispanic ethnicity). Parents of children with ASD were significantly less likely to be employed than parents of youth with asthma and control combined (OR: 14.2, p  < 0.001), and were more likely to have other difficulties with employment and productivity while at work. Public and employer policies to help mitigate these impacts could aid families in managing care for youth with ASD. Lay Summary: Caring for a child with a chronic health condition such as autism spectrum disorder (ASD) can interfere with parental employment in a number of ways. We found that parents of children with ASD are less likely to be employed, and when they are employed, many face challenges in managing productivity and caregiving. A detailed understanding of these impacts can guide clinical and employment policies to help families navigate the financial implications of a child's health condition.